Developing the new humanistic classroom: pedagogical mediations to promote critical thinking - Baraona Cockerell, Miguel (2023)
This article presents in a summary some pedagogical principles and educational practices for the development of the teaching experience within theframe of what we term as the new humanistic classroom, whether be it physical and/or virtual. This text begins with a very brief presentation of our understanding of humanism, New Humanism, The Tri Dimensional Paradigm (TDP), of New Humanism, in order to address in a summarized way, the 14pedagogical principles (14 PPS) of New Humanism derived from the TDP, which promote on a daily basis critical.